2017
DOI: 10.5603/gp.a2017.0108
|View full text |Cite
|
Sign up to set email alerts
|

Birth body length, birth body weight and birth head circumference in neonates born in a single centre between 2011 and 2016

Abstract: Objectives: Access to updated and accurate standards for local populations is important for the interpretation of body measurements in neonates and may have an impact on the doctor's recommendations for monitoring early childhood development.Study aim: to present individual mean values for the most prevalent body measurements (i.e. birth body length (BBL), birth body weight (BBW) and birth head circumference (BHC)) in neonates and compare them to the duration of pregnancy. Material and methods:The measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One study showed that males are more likely than females to be stunted at birth [2]. A longer duration of pregnancy has also been found to have a significant positive association with an infant's length at birth [11]. A previous study highlighted the need to consider maternal height-a potential indicator of a mother's nutritional status during childhood-as a proxy for intergenerational undernutrition that affects stunting [5].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that males are more likely than females to be stunted at birth [2]. A longer duration of pregnancy has also been found to have a significant positive association with an infant's length at birth [11]. A previous study highlighted the need to consider maternal height-a potential indicator of a mother's nutritional status during childhood-as a proxy for intergenerational undernutrition that affects stunting [5].…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies could be explained by our different patient population comprising only term fetuses without accompanying noncardiac or chromosomal defects, whose mothers had no concomitant diseases. Furthermore, the results may vary due to length measurement techniques provided in Poland with the use of a tape 31 . It is also worth noting, in contrast to other studies that the ethnicity was homogenously Caucasian.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the results may vary due to length measurement techniques provided in Poland with the use of a tape. 31 It is also worth noting, in contrast to other studies that the ethnicity was homogenously Caucasian. The differences may also result from the growth charts used and from the definition of "smallness" used, which, according to some authors, was < the 10 percentile, and according to others, was <2500 g. In our study, we used the Delphi criteria and WHO growth charts.…”
Section: Main Findingsmentioning
confidence: 83%
“…One study showed that infants boys are likelier to be born shortly than baby infant 10 . The longer gestational duration was also found to have a significant positive relationship with the baby's length at birth 11 . Meanwhile, research in Ethiopia showed that stunting was related to gender, pregnancy season, and birth weight 12 .…”
Section: Introduction Introductionmentioning
confidence: 84%